The indefatigable, itinerant school music teacher: Godwin Adedayo Dedeke (1921-1994) (2020)
The rise and development of Yoruba art music was influenced by the activities of European missionaries in Lagos and its environs, which began in the mid-nineteenth century. It manifested in the form of sacred music in the church, and secular music in the schools and society. This gave rise to composers and practitioners of art music, whose objective was to create a modern tradition of Nigerian art music. They were trained in local and overseas institutions and composed music patterned, not only along European music, but also in combination with African musical elements. Amongst these composers were T.K.E Phillips, Fela Sowande and Dayo Dedeke. Using the theory of cultural nationalism, this article studies the life and musical contributions of Godwin Adedayo Dedeke (1921-1994), a Yoruba art musician and frontline school music teacher, whose works and activities spanned various schools across South Western Nigeria. His work culminated in the publication of his popular song book Ma gbagbe ile in 1963. Oral interviews and focus group discussions were used to gather data, which was presented utilising content analysis. Ma gbagbe ile contains 36 sacred songs, as well as 14 secular songs. As a school music teacher, Dayo Dedeke taught the songs to various secondary schools across South-Western Nigeria. He also popularised Yorùbá choral music through radio and television choral music programmes for schools and colleges, titled ‘The Young Voices’.